Emir Abdelkader ’s Position On The Strife Of Sham And Its Impact On Modern Literature A Study In Textual Relations - boukezzoula, nadjat (El Omda in Linguistics and Discourse Analysis, 2023)
Al Emir is considered as a unique personality who is still the destination of many interested ones and researchers who have read about this feat hero, as they knew that behind his military victories and heroics, his brilliant thought and unique genius, as well as his personality that is merciful to the weak and the oppressed, embodied in his humanitarian situations. In adddition to his rescue of the dhimmis from the Christians in Damascus (exile) during the sedition that occurred in 1860. It is the culmination of his surprising and admirable noble atittudes , which have done their work in literature, blended with it, and penetrated the fabric of its texts. Writers and poets were affected by this noble stance, as we wrote poems, letters, speeches, and prose introductions that praise his deed and his benevolence, which spread to the world. Furthermore, this incident was evident in the letters of Al Emir and his speeches. Through our research, we aim to approach some of those literary texts that were affected by this human attitude, to identify the underlying human, civilizational and aesthetic dimensions in these texts in their interaction with the positions of Emir Abdelkader Al-Jazaery and in the interaction of these texts with each other.